2011
DOI: 10.1039/c1an15530j
|View full text |Cite
|
Sign up to set email alerts
|

On-chip sample pretreatment using a porous polymer monolithic column for solid-phase microextraction and chemiluminescence determination of catechins in green tea

Abstract: A porous polymer monolithic column for solid-phase microextraction and chemiluminescence detection was integrated into a simple microfluidic chip for the extraction and determination of catechins in green tea. The porous polymer was prepared by poly(glycidyl methacrylate-co-ethylene dimethacrylate) and modified with ethylenediamine. Catechins can be concentrated in the porous polymer monolithic column and react with potassium permanganate to give chemiluminescence. The microfluidic chip is reusable with high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…It is interesting to mention the study by Vidic et al comparing different glass surface treatment methods, which revealed that pretreatment with boiling water was enough for sufficient attachment of polymer to the capillary wall. In the case of HPLC format, several authors have used wall treatment to counter void formation and weak adhesion of the polymer to the wall, and in contrast with other studies and our results, it is clear that, as in case of capillaries, it is also important in HPLC format to find the important steps of the surface wall silanization methods. This is an interesting subject for future research and was not extensively investigated in this study.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…It is interesting to mention the study by Vidic et al comparing different glass surface treatment methods, which revealed that pretreatment with boiling water was enough for sufficient attachment of polymer to the capillary wall. In the case of HPLC format, several authors have used wall treatment to counter void formation and weak adhesion of the polymer to the wall, and in contrast with other studies and our results, it is clear that, as in case of capillaries, it is also important in HPLC format to find the important steps of the surface wall silanization methods. This is an interesting subject for future research and was not extensively investigated in this study.…”
Section: Resultscontrasting
confidence: 93%
“…Summarizing the literature search results for 2010–2012 (Thomson Reuters Web of Knowledge, topic “monolithic column,” November 5, 2012) and keeping in mind the surface treatment, it turns out that more than three‐fourths of the monolithic columns with conventional HPLC dimensions were prepared inside stainless‐steel column reservoirs without any surface treatment, and the whole contraction problem receives no attention in most of the papers , unless glass or silicosteel has been used as column material.…”
Section: Introductionmentioning
confidence: 99%
“…The epoxide groups of the (glycidyl methacrylate)-co-(ethylene dimethacrylate) column were allowed to react with ethylenediamine. A modified method described by Lin et al [25] was used to obtain monoliths with amine groups. Ethylenediamine solution was pumped through the (glycidyl methacrylate)-co-(ethylene dimethacrylate) monolith at room temperature at a flow rate of 0.1 mL min −1 for 30 min.…”
Section: Preparation Of Sers Columnmentioning
confidence: 99%
“…Other methods based on the oxidation of Ru(bipy) 3 2+ have been reported more frequently, such as photochemical or electrochemical . Other CL systems have also been reported, such as Peroxyoxalate (PO) , rhodamine or its derivatives , potassium permanganate , periodate , potassium ferricyanide , 1,10‐phenanthroline–H 2 O 2 , 1,1'‐oxalyldi‐4‐methylimidazole and bis (2‐carbopentyloxy‐3,5,6‐trichlorophenyl)oxalate 9,10‐diphenylanthracine and sodium hypochlorite . All of these reports are summarized in Table .…”
Section: System In Microfluidicsmentioning
confidence: 99%